Farmer surveys in Cambodia and Vietnam: cassava planting material use and exchange at national level with 4 district-level case studies - Delaquis, Erik; Andersen, Kelsey F.; Minato, Nami; Thuy, Cu Thi Le; Karssenberg, Maria Eleanor; Sophearith, Sok; Wyckhuys, Kris A.G.; Newby, Jonathan Craig; Burra, Dharani Dhar; Srean, Pao; Phirun, Iv; Niem, Le Duc; et al. (International Center for Tropical Agriculture, 2018)
The data includes national surveys of 15 districts in Vietnam and 16 districts in Cambodia, with 15 responses by district. Districts were selected based on high cassava production density and expert input from local government officials. National surveys covered the following themes: (a) respondent information, (b) seed use overview, and (c) field and household data. In addition to the aforementioned categories, the subnational surveys collected data on (d) quality, (e) affordability/profitability, and (f) information sources.